Crowdfunding : a guide to raising capital on the internet - Dresner, Steven, 1970- (Bloomberg financial series., 2014)
A groundbreaking book on the growing trend of crowdfunding Crowdfunding has gained considerable traction over the last few years. By combining the Internet/social media with equity-based financing, it is poised to usher in a new asset class that will change how early stage and small business financing transactions are consummated. Author Steven Dresner, Founder and CEO of DealFlow Media, understands the nuances of how crowdfunding can help companies gain much needed access to capital, and now he shares those insights with you. Engaging and informative, this book will serve the n.